SURROGATE MOTHER “RENTAL AGREEMENT MADE IN THE PRESENCE OF A NOTARY - Hudaya, Sonny Gondo; Adjie, Habib (IBLAM LAW REVIEW, 2024)
The practice of Surrogate Mothers according to Indonesian law gives rise to the problem that Positive Law in Indonesia does not yet recognize provisions regarding renting a womb (Surrogate Mother). This research aims to understand and comprehend Surrogate Mothers according to Indonesian law. This writing uses normative legal research methods with a type of legislative analysis approach (State approach). This research resulted in research that Indonesian law does not have regulations regarding the implementation of Surrogate Mother engagements. According to the provisions of the health law, surrogate motherhood cannot be carried out because of the clear regulations of the health law. Likewise with regulations in the realm of civil law, even though Article 1338 of the Civil Code states that "All agreements made legally apply to the law for those who make them," Article 1320 of the Civil Code provides conditions for the validity of an agreement, one of which is the existence of a halal cause. So that an agreement made must not conflict with legal regulations. So the implementation of Surrogate Mother cannot be implemented.